PENGUATAN DAYA SAING UMKM: MEMBANGUN LANDASAN KEUANGAN YANG STABIL MELALUI SISTEM INFORMASI AKUNTANSI - Saraswati, Esti; Yuliarti, Lusi; Kristianto, Giovanny Bangun (Bestari: Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service program aimed to enhance MSMEs' competitiveness through improved financial management by providing training on the Accounting Information System (AIS). The program involved 20 MSME business participants from the Banyumas Regency Micro, Small, and Medium Entrepreneurs Association (ASPIKMAS) in North Purwokerto. The goal was to increase financial literacy and facilitate the use of AIS for better financial record-keeping and reporting. The implementation included interactive workshops and ongoing mentoring. Evaluation results indicated a significant improvement, with participants' financial literacy rising from 40% in the pre-test to 85% in the post-test. Challenges encountered included low technological literacy and limited access to devices. However, continuous mentoring and strong partner support helped mitigate these issues. The program’s significance lies in its contribution to strengthening MSMEs' financial foundations and enhancing their capacity for digital financial management, ultimately boosting their competitiveness in the marketplace.